The Effect of Recruitment Activities on Social Media and Employer Branding on the Quality of Job Candidates - Yosep Perianto; Moch Nurhidayat; Retno Ayu Dewi Novitawati (International Research & Development for Human Beings (IRDH), 2026)
This study aims to analyze the influence of social media recruitment activities and employer branding on the quality of job candidates. The development of digitalization encourages companies to utilize social media as an effective recruitment tool to reach candidates more widely, quickly, and efficiently. Furthermore, employer branding is a crucial factor in building a company's image to attract qualified candidates. This study employed a quantitative approach with a survey method, distributing questionnaires to 183 respondents who met the research criteria. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results showed that social media recruitment activities had a positive and significant effect on the quality of job candidates. Employer branding also had a positive and significant effect on the quality of job candidates. Simultaneously, social media recruitment activities and employer branding had a significant influence on the quality of job candidates. These findings suggest that companies need to optimize the use of social media and strengthen employer branding to improve their ability to attract candidates who match the organization's needs. This research is expected to provide theoretical contributions to the development of human resource management science and serve as a practical reference for companies in designing effective digital recruitment strategies.